The Israeli electoral state of mind: security, discourse and leadership as components of 2015 elections - Alon Helled (QOE-IJES, 2018)
The 2015 Israeli general elections provide rare intellectual stimuli to trace and characterize some of the larger sociopolitical stances in Israeli society. Since Israeli politics has undergone many changes over the last decades, a focus on electoral moment unpacks the issues and general perception regarding geopolitics (i.e. the Israeli-Palestinian conflict) and the domestic health of the country (i.e. sociopolitical reforms and policy-developments). This paper aims at analyzing the three main dimensions, which were emphasized during the electoral campaign and the turnout, while it connects them with what we may refer to as the Israeli political "state of mind".